2006
DOI: 10.1007/s10562-005-9626-0
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Catalytic Cracking of n-hexane via Methanol Coupling Reaction Over HZSM-5 Zeolite Catalysts

Abstract: The coupling transformation of n-hexane and methanol over HZSM-5 has been investigated with a pulse-reaction system. In the temperature range of 400-500°C, kinetic data was collected and reaction order was determined. Compared with the pure n-hexane cracking, the increased rate constant and the lowered apparent activation energy clearly demonstrate an improvement of n-hexane activation using methanol as co-reactant and an increased contribution of faster bimolecular mechanism to the n-hexane transformation due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In our previous researches [13,14], it was observed that the introduction of methanol improved the conversion of n-hexane in the coupled system. Similarly, the coupled transformations of n-hexane and ethanol, as well as the uncoupled transformations of n-hexane, were performed over HZSM-5 catalyst at 400°C at different contact times.…”
Section: Coupled Transformation Of N-hexane and Ethanol At 400°cmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous researches [13,14], it was observed that the introduction of methanol improved the conversion of n-hexane in the coupled system. Similarly, the coupled transformations of n-hexane and ethanol, as well as the uncoupled transformations of n-hexane, were performed over HZSM-5 catalyst at 400°C at different contact times.…”
Section: Coupled Transformation Of N-hexane and Ethanol At 400°cmentioning
confidence: 95%
“…We previously investigated the coupled reaction of n-hexane and methanol over HZSM-5 zeolites [13], and found an improved conversion activity of n-hexane and an increased contribution of faster bimolecular mechanism to the n-hexane conversion by methanol. Furthermore, our recent work on this coupled system [14] has shown how the intermediates and products from the methanol acted as the active species for the initial activation and chain propagation of n-hexane and how the n-hexane in the coupled system accelerated the conversion of methanol.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis concerning energy compensation has been established to explain also the higher-conversion obtained in the hydrocracking of aromatics in a single step (on bifunctional Pt/HZSM-5 catalysts) compared with the conversion corresponding to the process in two consecutive steps, in which the dehydration is exothermic and the cracking of the resulting cycloalkanes is endothermic. 30,31 Based on the results of the integrated process formed by n-hexane and methanol as reactants, Chang et al 32 postulated that the intermediates (methoxy ions) in the transformation of methanol activate the mechanism of n-hexane bimolecular cracking by complementing the monomolecular cracking mechanism that occurs by n-hexane protonation on the Brönsted acid sites of the zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [20] related both mechanisms in combined reactions and suggested a faster route for the catalytic cracking of n-hexane due to the formation of intermediates from methanol. On the one hand, paraffin cracking mechanism follows a pathway involving the monomolecular cracking (via penta-coordinated carbonium ions that evolve towards light paraffins), the bimolecular cracking (via hydride transfer between the paraffin and an adsorbed carbenium ions) and the oligomerization-cracking (toward higher hydrocarbons and finally coke) [16,21,22].…”
Section: Introductionmentioning
confidence: 99%